La firma electrónica y su regulación en la Ley 59/2003, de 19 de diciembre, de Firma Electrónica - Berrocal Lanzarot, Ana I. (FORO. Revista de Ciencias Jurídicas y Sociales, Nueva Época, 2006)
The new Law 59/2003, as a response to the need to award safety to communications in the Internet and to reinforce the existing legal frame, incorporates several innovations related to the regulation of the electronic signature. So it is created a new concept of electronic signature demanded by the sector, the electronic qualified signature, which is compared functionally to the manuscript signature; a series of guarantees are demanded to expiring for the devices of creation of electronic signature; it is included inside the modality of documentary evidence to the support in which the signed information appears; a special legitimation is demanded to solicitors of taking responsibility of the custody of such information; and, there is established a regime applicable to the performance of legal persons signatories.